Pemanfaatan Dana Zakat Bagi Mustahiq Di Kabupaten Deli Serdang - Dilla Ayu Wardani; Mawaddah Irham (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
ABSTRAKThis study aims to determine: How to use zakat funds for mustahiq in Deli Serdang Regency. In order to create prosperity for the mustahiqof Deli Serdang Regency.This type of research is qualitative research using primary data in the form of interviews. Informants in this study were staff of BAZNAS Deli Serdang Regency and recipients of zakat. The data analysis technique in this study used descriptive analysis techniques, namely by describing, interpreting and describing the data collected systematically.The results of the discussion in this study are the zakat funds are very helpful for the mustahiq economy of Deli Serdang Regency. Some of them use the received zakat funds as a tool to meet their own basic needs and the basic needs of the people who are their dependents. In addition, half of the zakat funds received are used for productive activities, such as business capital, as savings. This productive behavior is in line with the function and purpose of zakat. Zakat is not only aimed at helping weak people from falling that is getting worse, but the main goal is so that humans are of higher value than wealth, so that humans do not become slaves to wealth.Key words : zakat, mustahiq, BAZNAS ABSTRAK       Penelitian ini bertujuan untuk mengetahui: Bagaimana pemanfaatan dana zakat bagi mustahiq di Kabupaten Deli Serdang. Agar terciptanya kesejahteraan bagi mustahiq Kabupaten Deli Serdang.       Jenis penelitian Kualitatif  menggunakan data primer berupa wawancara. Informan penelitian ini ialah staf-staf BAZNAS Kabupaten Deli Serdang dan penerima zakat. Teknik analisis deskriptif, yaitu menguraikan, dan menggambarkan data yang terkumpul.       Hasil pembahasan tersebut bahwa dana zakat sangat membantu perekonomian mustahiq Kabupaten Deli Serdang. Sebagian dari mereka menggunakan zakat yang diperoleh sebagai alat memenuhi kebutuhan esensial mereka sendiri dan kebutuhan dasar individu yang menjadi tanggungan mereka. Selanjutnya, dari dana zakat digunakan untuk kegiatan yang bermanfaat, seperti modal usaha, sebagai dana investasi. Cara berperilaku yang bermanfaat ini sesuai dengan kemampuan dan motivasi di balik zakat tidak hanya ditujukan untuk membantu individu yang lemah dari kejatuhan yang semakin parah, tetapi tujuan utamanya adalah agar manusia lebih berharga daripada kekayaan, sehingga manusia tidak menjadi tawanan kelimpahan.Kata kunci : Zakat, mustahiq, BAZNAS